Kinetics And Modelling For The Production Of (S)-Ibuprofen Acid - Gonawan, Fadzil Noor (2012)
The effect of co-solvents and bases have been investigated in Candida rugosa lipase (CRL)-catalyzed hydrolysis of (R,S)-2-ethoxyethyl ibuprofen ester in biphasic water-isooctane medium. A high log P and low pKa values of co-solvent has reduced the reaction rate for the production of (S)-ibuprofen acid. Moreover, the hydrolysis process shows an optimum performance at only 2% (v/v) dimethyl sulfoxide (DMSO) and at the reaction temperature of 30°C. The addition of 2% (v/v) DMSO has increased the conversion of substrate and further increase in the concentration of DMSO has resulted in a low initial reaction rate and conversion of substrate, however gives a high enantiomeric excess of the product (eeP).